2022
DOI: 10.14569/ijacsa.2022.0130970
|View full text |Cite
|
Sign up to set email alerts
|

Smart Greenhouse Monitoring and Controlling based on NodeMCU

Abstract: Food security is one of the major rising issues as the human population is larger and the land available for cultivation is smaller, as well unassured affairs happened often in society especially in the current CoVID-19 rapidly spread days. To mitigate this condition, further improve the yields and quality of food, this paper proposed a smart and low-cost greenhouse monitoring and control system, which mainly consists of sensors, actuators, LCD display and microcontrollers. DHT22 sensor is used to get the surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The results of the system were promising, and the researchers concluded that it could be used in other greenhouses. Y. Liu [14] Proposed a smart greenhouse to monitor the ambient temperature and humidity of the greenhouse. A DHT22 sensor was used to collect both temperature and humidity, and an ESP8266 microcontroller was utilized to collect the sensor data, which was then transmitted and stored in the cloud database via a wireless network.…”
Section: Related Workmentioning
confidence: 99%
“…The results of the system were promising, and the researchers concluded that it could be used in other greenhouses. Y. Liu [14] Proposed a smart greenhouse to monitor the ambient temperature and humidity of the greenhouse. A DHT22 sensor was used to collect both temperature and humidity, and an ESP8266 microcontroller was utilized to collect the sensor data, which was then transmitted and stored in the cloud database via a wireless network.…”
Section: Related Workmentioning
confidence: 99%
“…ThingSpeak which is a cloud platform predominantly used to process the sensor data and visualizing the result out of sensory tDCS prototype. Using the same technologies, crop health can be maintained by ensuring greenhouse conditions with help of IoT sensors and processing the output over ThingSpeak platform [22].…”
Section: A Related Workmentioning
confidence: 99%